Bridge to silence. (S.l. : Fries Entertainment, 1988)
Peg verliest haar man, die net als zij gehoorgestoord is, in een auto-ongeval. Het gaat om een versie die gedubd is in het Frans.
John and Peg are both deaf and they have a six year old daughter, Lisa. On their way to Peg's parents they have a car accident and John is killed. Peg has a nervous breakdown and Peg's mother temporarily takes care of Lisa. But when Peg recovers, her mother won't let her take care of her daughter and files a lawsuit to become Lisa's legal guardian.